Benign vascular tumors and vascular malformations in childhood: a retrospective analysis of 1127 cases - Akyüz, Canan; Yarış, Nilgün; Kutluk, M. Tezer; Büyükpamukçu, Münevver (The Turkish Journal of Pediatrics, 1997)
Vascular lesions in childhood are classified as vascular malformations and hemangiomas. Vascular malformations are congenital abnormalities thought to arise from defects during embryological development of vascular tissue. Hemangiomas are benign tumors of vascular endothelium and can spontaneously become involuted in almost all cases. One thousand one hundred and twenty-seven patients with vascular lesions were followed by the Department of Pediatric Oncology, Hacettepe University, for 19 years. Diagnosis was based mainly on history, clinical condition and follow-up data in 98.2 percent of cases. The distribution of the vascular lesions was as follows: 969 patients had hemangiomas, 120 had lymphatic malformations, 18 had combined vascular malformations, 11 had venous malformations, six had port-wine stain, and three had angiokeratoma. Except for ten cases with Klippel-Trenaunay Weber syndrome, vascular malformations were not accompanied by any syndrome.